The Influence of Love of Money, Machiavellianism, and Idealism on the Ethical Perception of Accounting Students with Religiosity as a Moderating Variable - Rizkiza Aurin; Afrizal Afrizal; Yuliusman Yuliusman (Journal of Management Economic and Financial, 2025)
An accounting student's ethical outlook is crucial for future professional integrity. This study aims to analyze how the love of money, Machiavellianism, and idealism influence the ethical views of accounting students, with religiosity as the moderating variable. The research method used is quantitative, with a survey conducted among accounting students at the University of Jambi, class of 2021 and 2022. A sample of 224 students was selected using the Slovin formula. Hypothesis testing was performed using multiple linear regression and moderated regression analysis (MRA). The results of the study show that the ethical views of accounting students are negatively influenced by the love of money and Machiavellianism, which tend to undermine student ethics. In contrast, idealism significantly enhances the ethical views of accounting students. However, religiosity does not have a significant effect on the relationship between the love of money, Machiavellianism, and idealism with the ethical views of accounting students. These findings suggest that schools need to improve the teaching of ethics in accounting education to produce honest professionals.